2002
DOI: 10.1002/jcb.10130
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in collagen gene induces cardiomyopathy in transgenic mice*

Abstract: In many remodeling tissues, such as the heart, collagen degradation to provide new integrin-binding sites is required for survival. However, complete loss of integrin signaling due to disconnection from extracellular matrix (ECM) leads to apoptosis and dilatation. To test the hypothesis that a mutation in type I collagen gene induces cardiomyopathy, we employed a metalloproteinase-resistant collagen mutant homozygous transgenic male (B6,129-Colla-1) and compared with age-sex matched wildtype C57BL/J6 control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…21 Collagen type I is the most abundant collagen type in the heart, constituting approximately 50%-80% of the extracellular matrix (ECM). 4 Miller et al 22 reported that transgenic mice overexpressing the collagen I gene exhibited enhanced cardiac fibrosis and dysfunction. Consistent with previous studies, we noted marked fibrosis and increased a-SMA, and collagen I protein expression in the pressure-overloaded myocardium.…”
Section: Discussionmentioning
confidence: 98%
“…21 Collagen type I is the most abundant collagen type in the heart, constituting approximately 50%-80% of the extracellular matrix (ECM). 4 Miller et al 22 reported that transgenic mice overexpressing the collagen I gene exhibited enhanced cardiac fibrosis and dysfunction. Consistent with previous studies, we noted marked fibrosis and increased a-SMA, and collagen I protein expression in the pressure-overloaded myocardium.…”
Section: Discussionmentioning
confidence: 98%
“…Increased basal levels of extracellular matrix degradation have been attributed to the development of cardiomyopathy in collagen I mutant mice [60]. Careful study of collagen I mutant mice revealed that turnover of extracellular matrix components is strongly interwoven and alterations in extracellular matrix composition may provoke cardiac dysfunction [58].…”
Section: Discussionmentioning
confidence: 99%
“…This drug had minimal effects on cardiovascular function in mice [26]. The aortic blood pressure, heart rate (HR), and systolic and diastolic blood pressure (SBP, DBP) were measured by a PE-10 catheter in aorta through the right common carotid artery [27]. After arterial pressure measurements, the catheter was advanced to LV and LVP, EDP and dP/dt were measured.…”
Section: Methodsmentioning
confidence: 99%